2011
DOI: 10.1525/bio.2011.61.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting Environmental Hazards and the Application of Risk Maps to Predator Attacks on Livestock

Abstract: Environmental hazards are distributed in nonrandom patterns; therefore, many biologists work to predict future hazard locations from the locations of past incidents. Predictive spatial models, or risk maps, promise early warning and targeted prevention of nonnative species invasion, disease spread, or wildlife damage. The prevention of hazards safeguards both humans and native biodiversity, especially in the case of conflicts with top predators. Top predators play essential ecological roles and maintain biodiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
130
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(134 citation statements)
references
References 40 publications
4
130
0
Order By: Relevance
“…We generated univariate linear regression models to examine which landscape attributes were strong predictors of kill probability. Following standard methods (Garamszegi 2010;Treves et al 2011), we ran Spearman correlations between variables and built global models for livestock species that included the variables that were significant in the univariate regression and not correlated with more significant variables (r s \ 0.6). These requirements excluded the variable distance to nonforest, which was correlated with distance to village (r s = 0.7) and distance to very dense forest (r s = 0.7).…”
Section: Statistical Analysis and Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We generated univariate linear regression models to examine which landscape attributes were strong predictors of kill probability. Following standard methods (Garamszegi 2010;Treves et al 2011), we ran Spearman correlations between variables and built global models for livestock species that included the variables that were significant in the univariate regression and not correlated with more significant variables (r s \ 0.6). These requirements excluded the variable distance to nonforest, which was correlated with distance to village (r s = 0.7) and distance to very dense forest (r s = 0.7).…”
Section: Statistical Analysis and Modelingmentioning
confidence: 99%
“…livestock husbandry techniques (Wikramanayake et al 1998;Miller 2015). Many previous studies on humancarnivore conflict have focused on depredation by a single carnivore species (usually a high-priority species of conservation concern) on all livestock species generally, which can obscure unique risk gradients for individual livestock species from specific carnivores (Treves et al 2011;Lichtenfeld et al 2014;Athreya et al 2014;Miller et al 2015). Differences between the body sizes, anti-predator defenses, and grazing requirements of livestock species result in distinct levels of vulnerability to wild carnivores (Seidensticker 1976;Sinclair et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Esterhuizen & Norton, 1985) have investigated the spatial distribution of leopard (Panthera pardus) predation, the associated livestock losses and the management responses to leopard depredation (McManus, Dickman, Gaynor, Smuts & Macdonald, 2014). This information is essential in improving species management and reducing conflict (Treves et al, 2011). The present study investigated the conflict between leopards and livestock in the Baviaanskloof Mega-Reserve (BMR), South Africa.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, a large body of literature has focused on identifying hotspots of predator-livestock conflict (Treves, Martin, Wydeven & Wiedenhoeft, 2011;Ward, Levin, Lance, Jeffries & Acevedo-Gutiérrez, 2012). For example, Stahl, Vandel, Herrenschmidt & Migot (2001) showed that 33-69% of Eurasian lynx (Lynx lynx) attacks on live-stock were localized to 0.3-4.5% of the total area where lynx predation occurred.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation